PRODUCT, PROCESS, AND KNOWLEDGE INNOVATION HAVE A MEDIATING ROLE IN THE RELATIONSHIP BETWEEN HRM PRACTICES AND SUSTAINABLE ORGANIZATIONAL PERFORMANCE - Hammad Zafar; Muhammad Azeem Khan; Sheikh M.Fakhre Alam Siddiqu (Policy Research Journal, 2025)
This study examines the relationship between sustainable organizational performance (SOP) and human resource management (HRM) practices in the banking industry, with an emphasis on the function of organizational innovation (OI) as a mediator. By encouraging innovations in products, processes, and information, the study explores how HRM practices such employee staffing, performance management, staff development, and compensation affect SOP. Theories such as the Knowledge Based View (KBV) and Resource Based View (RBV) highlight how crucial HRM is to the success of a business. Data on HRM and SOP were gathered for this quantitative study from 20 Karachi branches of five Pakistani banks using 106 questionnaires. The impacts were estimated using partial least squares structural equation modeling (PLS). With the exception of employee staffing, all HRM procedures, including performance management, staff development, and pay and benefits, had a favorable impact on SOP. Only three aspects of HRM practices aside from process were positively correlated with OI, which was correlated with SOP when indirect linkages were examined. The survey highlights that while some employees in Pakistan's banking industry try to adopt new, creative working methods, many employees continue to operate in traditional ways. This last group of employees contributes significantly to SOP. The study exclusively utilized quantitative data collected from employees for analysis, omitting the perspectives of bank leaders. By investigating the mediating function of organizational innovation in the connection between HRM practices and sustainable organizational performance, this study offers a fresh viewpoint. The study closes a large vacuum in the literature by concentrating on the banking industry in an emerging economy and providing context-specific insights. The results offer practitioners insightful advice on how to improve HRM procedures and encourage creativity, which will ultimately boost organizational efficacy and competitiveness.